Experimental and modeling investigation on the viscoelastic-viscoplastic deformation of polyamide 12 printed by multi jet fusion - Chen, Kaijuan (2022)
The viscoelastic-viscoplastic deformation of Multi Jet Fusion-printed polyamide 12 (MJF PA12) was investigated with experimental and numerical approaches. Multi-loading–unloading–recovery tests were conducted to distinguish between the viscoelastic and viscoplastic deformations. The influence of the void defects on deformation of PA12 was investigated through the microcomputed tomography (μCT) and field emission scanning electron microscope. A finite-strain viscoelastic-viscoplastic constitutive model based on the logarithmic stress rate for the matrix of MJF PA12 was developed within the thermodynamic framework as well as an introduction of the accumulated plastic deformation–induced damage into the proposed model. A representative volume element was modeled based on the μCT results of MJF PA12. The simulated results, such as stress–strain and strain–time curves, agreed with the experimental results. Moreover, the model revealed the mechanism that the low tensile ductility of MJF PA12 is caused by the increase in strain localization and narrowing of the shear band.